The Dy2O3 Effect Study on Spectroscopy and Optical Properties of PbiNaGd Glass for Optical Amplification. (January 2020) - Situmorang, R; Rahmaniar; Panggabean, D D.; Sarumaha, C.; Kaewkhao, J; Sunaryono; Rajagukguk, J
Abstract: The medium glass was made from chemical compounds with the compositions (70-x) P2 O5 - 10Bi2 O3 - 10Na2 O - 10Gd2 O3 - xDy2 O3 (where x = 0; 0.05; 0.1; 0, 5; 1.0; 3.0 (mol%)) which was doped by active ion xDy2O3. All of proposed chemical compounds are in the form of powder with the mass of 20 grams of mixture in an alumina crucible and prepared by melt-quenching method. The glass has been obtained with a size (3x10x10) mm 3 and smoothed to get a flat surface and high transparency. Optical properties of glass samples Dy:PBiNaGd determined by measuring by absorption spectrum and spectrophotometer at area visible with different concentration. Analysis indicates eleven inhomogeneous displacement bands at various positions and intensities with hypersensitive transitions at 1274 nm ( 6 H15/2 → 6 F11/2 ). Emission spectrum in medium glass Dy:PBiNaGd is supported using excitation wavelength (λeks) 350 nm and indicated that the highest intensity is in Dy:PBiNaGd4 where there four transition band emisions are namely 4 H9/2 → 6 H13/2 (483 nm), 4 H9/2 → 6 H11/2 nm), 4 H9/2 → 6 H9/2 (661 nm) and 4H9/2 → 6H6/2 (750 nm).